Distinct dormancy progression depending on embryonic regions during mouse embryonic diapause†. Issue 5 (1st February 2019) - Kamemizu, Chizuru; Fujimori, Toshihiko
Abstract: Many mammalian species undergo embryonic diapause and suspend development at the blastocyst stage before implantation, which is also known as delayed implantation. We studied the process of how mouse embryos enter a dormancy status at a cellular level. Immunofluorescent analysis of differentiation markers for epiblast, primitive endoderm, and trophectoderm suggested that cell differentiation status was maintained during 7 days in diapause. To understand the progression of cellular dormancy during diapause, we examined the expression of a transgenic cell cycle marker Fucci2 and Ki67 by antibody staining, in addition to direct counting of nuclei in embryos. From these analyses, embryos during diapause were categorized into four stages by cell number and cell cycle. Cell cycle arrest occurred from the ab-embryonic region and from the trophectoderm to the ICM in the embryonic side. We also observed cell cycle transition by live imaging of Fucci2 embryos during the reactivation in culture from dormant status. Cell cycle was initially recovered from the embryonic side of embryos and eventually spread throughout the whole embryo. We also found that embryos in later stages of diapause required a longer period of time for reactivation. From these observations, it was shown that entrance into and exit from dormant status varied depending on cell types and location of cells in an embryo. These results suggest that embryonic diapause includes multiple steps and the mechanisms involved in cellular dormancy may be distinct between embryonic regions. Abstract : Dormancy progression during mouse embryonic diapause was categorized into four stages by cell number and cell cycle. Entrance into and exit from dormant status varied depending on cell types and location of cells in an embryo.